2022
DOI: 10.1007/s00167-022-07163-4
|View full text |Cite
|
Sign up to set email alerts
|

Posterior tibial slope and meniscal slope correlate with in vivo tibial internal rotation during running and drop jump

Abstract: Purpose The relationship between tibial bony and meniscus anatomy and knee kinematics during in vivo, high-impact activities remains unclear. This study aimed to determine if the posterior tibial slope (PTS) and meniscal slope (MS) are associated with in vivo anterior-posterior translation and internal tibia rotation during running and double-leg drop jumps in healthy knees. Methods Nineteen collegiate athletes performed fast running at 5.0 m/s on an instrumented treadmill and double-leg drop jump from a 60 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…The LPTS was measured using a sagittal plane centered in the lateral tibia as previously described (Fig. 2A) [35]. The MTP depth was measured in the sagittal plane centered in the medial tibia as the distance between the most anterior to most posterior points of the medial tibial plateau and a line parallel to this and passing through the deepest part of the tibial concavity [30] (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LPTS was measured using a sagittal plane centered in the lateral tibia as previously described (Fig. 2A) [35]. The MTP depth was measured in the sagittal plane centered in the medial tibia as the distance between the most anterior to most posterior points of the medial tibial plateau and a line parallel to this and passing through the deepest part of the tibial concavity [30] (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown increased interest in the association between bony morphology and knee kinematics [4,18,23,35]. Speciically, a steeper LPTS was associated with more tibial internal rotation during drop jumps [23,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For dogs with CCL rupture, tibial plateau levelling osteotomies (TPLOs) are the standard of care over ligament reconstruction. Tibial osteotomies have been reported in humans to correct increased tibial slope, a known intrinsic risk factor for ACLR failure [18, 40]. Zoobiquity is the term used to describe the collaboration between the human and veterinary professions to advance scientific understanding in both fields [10].…”
Section: Editorialmentioning
confidence: 99%
“…Extrinsic factors, such as type of sport and physical preparation, could be optimized by adjusting rehabilitation and preparatory programs [2, 10, 21], though there is limited evidence regarding the efficacy of such methods at reducing failure rates. Intrinsic factors, including anatomic, genetic, and hormonal aspects, should also be considered, notably the posterior tibial slope (PTS) [23, 30, 31], as it increases anterior tibial translation [7, 13, 28] and exacerbates anteroposterior tensions within the ACL [12, 20]. The association between excessive PTS and ACLR failure has been demonstrated in both short‐ and long‐term studies [3, 25].…”
Section: Introductionmentioning
confidence: 99%